A critical analysis of factors affecting photovoltaic-green roof performance. (March 2015) - Lamnatou, Chr.; Chemisana, D.
Abstract: Photovoltaic (PV)-green roofs combine PVs with green roofs, are a new tendency in the building sector and they provide additional benefits (in comparison with the simple green roofs) such as in situ production of electricity. The present study is a critical review about multiple factors which are related with PV-green roofing systems. Representative investigations from the literature are presented along with critical comments. The studies reveal that plant/PV interaction results in PV output increase depending on parameters such as plant species, climatic conditions, evapotranspiration, albedo, etc. Furthermore, by comparing a PV-green roof with a PV-gravel one from environmental point of view, it can be seen that the PV-green system, on a long-term basis, compensates its additional impact due to its higher production of electricity. Moreover, in the frame of the present study, a systematic classification of Mediterranean plant species in terms of their appropriateness for PV-green roofs is also conducted. The results reveal that PV output increase which is provided by PV-green roofs depends on several factors and among the studied plant species, Sedum clavatum shows the best interaction with the PVs and the building. Experimental results and findings about the environmental profile of PV-green roofs are also presented and critically discussed. Conclusively, PV-green roofing systems are promising, especially for warm climates.